2021
DOI: 10.1186/s12610-021-00134-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis and redox state of the testicles in nandrolone decanoate and swimming treated adult male rats

Abstract: Background During the last decades, the abuse of anabolic androgenic steroids (AASs) has become popular among professional and recreational athletes. The abuse of AASs leads to decreased levels of sex hormones, but the available literature a gives very small pool of data regarding the effects of swimming alone or combined with AASs on testicle tissue. The aim of this study was to investigate the effects of four-week administration of nandrolone decanoate and swimming training alone or in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…During the last few decades, nandrolone decanoate has become one of the most frequently abused AAS among professional and recreational sportsmen [ 21 ]. Regular physical activity, as a modern way of life, has positive effects on many organ systems, especially on the cardiovascular system and metabolic disorders [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few decades, nandrolone decanoate has become one of the most frequently abused AAS among professional and recreational sportsmen [ 21 ]. Regular physical activity, as a modern way of life, has positive effects on many organ systems, especially on the cardiovascular system and metabolic disorders [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that abuse of AAS causes adverse effects on the liver, such as cholestatic jaundice, peliosis hepatis, hepatocellular hyperplasia, and hepatocellular adenoma [ 19 ]. Furthermore, in regard to the male reproductive system, the abuse of these agents may induce testicular atrophy [ 20 ], followed by the decrease of the diameter of seminiferous tubules and the increase of the interstitium of the testicles [ 21 ], impotence, and benign prostate hypertrophy [ 20 ]. Most recently, it has also been shown that nandrolone causes harmful effects on pituitary LH and FSH gonadotrophic cells, reflected by the reduction in volume density and number of cells per mm 2 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Binding sites were visualized with 0.05% diaminobenzidine (DAB; Serva, Heidelberg, Germany). The sections were contrasted with hematoxylin, rehydrated in increasing alcohol concentrations (70–100%), cleared in xylene, and mounted with DPX (Sigma-Aldrich, St. Louis, MO, USA) [ 22 ]. Images of the tissue sections were captured using a digital camera attached to a light microscope Olympus BX51 (Olympus Life and Material Science Europa GmbH, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Images of the tissue sections were captured using a digital camera attached to a light microscope Olympus BX51 (Olympus Life and Material Science Europa GmbH, Hamburg, Germany). Morphometric analysis of collagen content and immunopositivity evaluation of the COX-2 in the aphthae were performed using the software program Image Pro-Plus (Media Cibernetics, Rockville, MD, USA) according to previously described methodology [ 22 , 23 ]. Results are presented as percentages [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation